The Cavern Concept of Main Character in Beauty and The Beast - Mella Nur Mauliah; Tenny Sudjatnika (CALL, 2020)
Literature is a fiction in which the author has freedom in expressing their imagination. In viewing a film, the audience can represent the film according to what they see.  This can be seen from the story line, moral massage, character, and so on. The character in a literary work elevates the aesthetic value, any character can be described by the author. It can be contained in a literary works, because it is an idea or imagination of someone to created an aesthetic purposes. The ugliness in the character it is called as grotesque. The grotesque character cause their alienation from his society, because the structured of body in ugly or odd. Researcher look for data relating to the question of the problem, how the of Cavern Concept in Beauty and The Beast. In this study, researcher used descriptive methods according to Suryana (2010:20) “metode yang digunakan untuk mencari unsur-unsur, ciri-ciri, sifat-sifat suatu fenomena. Metode ini dimulai dengan mengumpulkan data, menganalisis data dan menginterpretasikannya.” These conflicts to revealing the cavern concept includes: (1) condemnation of a Prince become an ugly figure. (2) transformation into to a Beast. (3) character’s emotional changes, because he as a Beast. (4) beast’s alienation from his environment or his world.